Studies on the effect of hydrogen ion concentration of extender on semen characters of Murrah buffalo bulls - GOKHALE, S B; MUSHTAQUE, M; PHADKE, N L; DINDORKAR, C V; AMBHORE, G S (The Indian Journal of Animal Reproduction, 2023)
The effect of semen extender Hydrogen Ion Concentration (pH) on seminal characteristics of 27 Murrah buffalo bulls collected during the period from 1999 to 2001 were studied for Ejaculate volume, Initial motility, sperm concentration, pre-freezing and post thaw motility, livability and sperm head, midpiece and tail abnormalities. The mean ejaculate volume, initial motility, spem1 concentration, pre-freezing and post-freezing motility was 6.35±0.09 ml, 87.66±0.65%, 1146.42±21.65 (106/ml), 86.57±0.15% and 64.80±0.’36%, respectively. The ejaculate volume was higher in winter and initial, pre and post thaw motility in summer. Ejaculate volume and sperm concentration was lowest in summer. Effect of year and season of collection and the associated effect of the age of the bull and the sperm concentration were not important in pre-freezing but had significant effect on post thaw motility. The effect of bulls and extender pH groups and the associated effect of ejaculate volume and initial motility were needed to be considered for pre-freezing while sperm concentration in postthaw motility. The mean live and dead sperm % were observed to be 79.99±0.80 .and 19.88±0.8% respectively. The head, midpiece and tail abnormalities were 1.70±0.09, 0.19±0.03 and 3.79±0.15%, respectively. Higher live sperms and lesser sperm abnormalities were observed when the pH of extender was between 6.7 to 6.8. The correlations between initial, pre and post thaw motility for different seasons were calculated and were generally significant. It was concluded that while freezing semen in Murrah buffaloe, the pH of extender should be between 6.7 to 6.8. The results also indicated necessity of further studies on microclimate of semen during freezing and for existing methods of estimation of sperm concentration to achieve higher post thaw motility.